Food insecurity is associated with diet and bone mass disparities in early adolescent males but not females in the United States - Eicher-Miller, H.; Mason, A.; Weaver, C.; McCabe, G.; Boushey, Carol (American Society for Nutrition, 2011)
Food insecurity is associated with decreased nutrient intake and poor health and possibly low bone mass in children. The purpose of this study was to formally investigate the relationship of diet, bone mass, and food insecurity among children aged 8-19 y (n = 5270). The data used in this cross-sectional study were drawn from children participating in the NHANES 2001-2004. Data were collected from homes and NHANES mobile examination centers across the United States. Food security status was classified using the US Children's Food Security Scale and the US Household Food Security Scale. Dietary measures were quantified by 24-h dietary recall and bone mineral content (BMC) was determined with whole body DXA. Results indicated that males 8-11 y from households with food insecurity among children were 2.5 times [OR = 2.5 (95% CI = 1.1-5.8)] more likely to have fewer than the USDA Food Guide recommended servings of dairy foods, 2.3 times [OR = 2.3 (95% CI = 1.3-4.0)] more likely to have less than the estimated average requirement for calcium intake, and more likely to have a significantly lower estimated total body (P = 0.04), trunk (P = 0.05), lumbar spine (P = 0.02), pelvis (P = 0.05), and left arm (P = 0.05) BMC compared with males 8-11 y old from households with food security among children. Calcium-related dietary factors and BMC did not differ among females by food security status. These results are evidence that health disparities persist among 8- to 11-y-old, food-insecure boys. Successful interventions to improve diet and bone health and reduce food insecurity among children are a continuing need in the United States.